Suicide in Palestine: Narratives of Despair by Nadia Taysir Dabbagh (Northampton, MA: Olive Branch Press, 2005. 265 pages.) (American Journal of Islam and Society, 2005)
Within the context of Islamic thought, suicide has met both tolerance andresistance and has spawned two cultural categories: suicide and martyrdom.Nadia Taysir Dabbagh approaches the issue with a dexterity honed by medicalexperience, and her insightful analysis of the two concepts reveals thatsuicide is perceived as a private act condemned by society and religion, whilemartyrdom is a public act exalted for the greater good. The fusion of theoriesplucked from psychiatry, anthropology, and psychology and then coupledwith compelling case studies conducted in Ramallah and Gaza creates a coveragethat treads the line between objective analysis and morbid fascination,as her research contributes a reasoned account of a startling trend largely lostin a region immersed in its tumultuous past and present and uncertain future.This book is the product of an intercalated M.B.–Ph.D. program submittedto the Psychiatry Department at University College London. The introductorychapter incorporates an elucidated methodology that identifies biological,social, and psychological study approaches, with the primary systemof analysis resting on the latter. This person-centred technique perceives suicideas an individual phenomenon linked to risk factors (e.g., depression,anxiety, and stressful life events) and associations. Likewise, the socialapproach favors a broader angle and associates suicide with such social conditionsas unemployment, domestic violence, and sociopolitical protest. Thebiological approach draws a correlation between affective disorders, such asbipolar disorder, and suicide. Eminent suicidologists, such as Michael Kral,Silvia S. Canetto, and David Lester, who assert that suicidal behavior shouldbe placed in its cultural as well as social context, provide the publication’stheoretical foundation ...